2020
DOI: 10.1097/ico.0000000000002296
|View full text |Cite
|
Sign up to set email alerts
|

Ethics in Eye Banking: Understanding Professional Attitudes Toward Industry Changes

Abstract: Purpose: To describe the ethical attitudes of corneal surgeons and eye bank leadership toward for-profit entities in corneal donation, processing, and distribution. Methods: Fifty postfellowship corneal surgeons practicing in the United States and 25 eye bank leaders (eg, eye bank directors, CEOs, or presidents) for the Eye Bank Association of America–accredited eye banks completed a 22-question interview, focusing on corneal donation industry changes, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…5 All but one EB organization in the world functions as a nonprofit organization 6 ; however, since for-profit emergence in 2016, 6 such profit models have been, and remain, widely contested in the eye tissue and eye care space. 7–9 In addition, we also note that third-party distributors (brokers) and transplant facilities may or may not be for-profit.…”
Section: Contemporary Eb Business Modelsmentioning
confidence: 99%
“…5 All but one EB organization in the world functions as a nonprofit organization 6 ; however, since for-profit emergence in 2016, 6 such profit models have been, and remain, widely contested in the eye tissue and eye care space. 7–9 In addition, we also note that third-party distributors (brokers) and transplant facilities may or may not be for-profit.…”
Section: Contemporary Eb Business Modelsmentioning
confidence: 99%
“…Profiteering from end‐of‐life donations is widely condemned, 18,20 and illegal in many jurisdictions 21 . Therefore, eye banks are universally non‐profit‐organisations.…”
Section: Introductionmentioning
confidence: 99%
“…However, this paradigm changed when a USA eye bank split their model in 2016 into a non‐profit recovery arm that subsequently transferred the donation to their spin‐off ‘for‐profit partner’ 22 with profits transferred to shareholders 9,17 . Since inception, this model has been globally condemned in the eye tissue and eye care field 20,23–25 . Its emergence is at odds with the wider eye tissue and eye care sector, and does not meet the recommendations outlined in The Barcelona Principles, 26 the GAEBA Commercialisation Statement 27 and the ICO Statement of 2017 28 .…”
Section: Introductionmentioning
confidence: 99%
“…10 The entry of for-profit entities into eye banking in the United States is a complex issue with ethical implications. Empirical ethics research, such as that by Ahmad et al (2020), helps to identify current perceptions of this contentious issue. However, determining the ethics of for-profit entities in eye banking requires normative ethics research.…”
mentioning
confidence: 99%
“…Ahmad et al 1 reported the results of a well-conducted survey of practicing cornea specialists and nonphysician eye bank leaders regarding the entrance of for-profit entities into eye banking in the United States. They identified several concerns that are held by corneal surgeons and eye bank leaders and provided interesting findings regarding differences in beliefs and attitudes between and within each group.…”
mentioning
confidence: 99%